Purposes and practices of youth work supervision: A narrative review - Lee, Kwan Meng; Krauss, Steven Eric; Consultancy, Dato’ Wasitah (Institute for Youth Research Malaysia, 2023)
Youth development is a critical component of the ecosystem of human society. Young people not only inherit but also play a crucial role in determining a nation's future progress, growth, and development. Youth workers are responsible for delivering quality services to youth through their engagement with them in diverse program settings and employment situations. Therefore, youth workers must be equipped with multiple skill sets to effectively facilitate youth development using different approaches. Proper supervision of youth workers is, therefore, a vital part of youth work practice. The role of supervisors in guiding youth workers aims to help them effectively nurture youth and unleash their full potential. Given the lack of clarity in the literature on the core purpose and practices of youth work supervision, this paper examines basic definitions of supervision, its functions, selected models of practice, and its importance in the youth work profession. A clear understanding of what youth work supervision is, its features, and importance to youth work practice can provide greater clarity for the profession to ensure its role within the developing profession.